Development and Application of Geological Survey Information Technology in CGS - Liu, Jia; Liu, Rongmei; Tan , Yongjie; Li , Fengdan; Wen, Min; Jin , Xi (Thai Geoscience Journal, 2024)
Geological informatization has undergone three development periods, namely digitization period, networking period, and intelligence (big data) period. The paper reviewed the role China Geological Survey (CGS) has played in the course and summarized major contributions over the past two decades. For fully utilizing the massive geodata for better supporting social and economic development, CGS conducted research and development of geo-information technologies, such as various software tools by adopting the current popular GIS, database and computer technologies, the upgraded Digital Geological Survey System (DGSS) based on cloud computing, big data and AI application, the national geodatabase system, the model and standard system, and the national geological database-GeoCloud 3.0. CGS also participated in several international cooperative programs, e.g. the Deep-time Digital Earth (DDE) and International Geoscience Program (IGCP), which promoted the progress of geoinformation technology in the world at large. In the new era, CGS has to conquer a series of obstacles to ensure secured data management, high level of data integration, guaranteed data quality and intelligent services.